2012
DOI: 10.1007/s00590-012-0982-3
|View full text |Cite
|
Sign up to set email alerts
|

Study on outcome of fracture shaft of the humerus treated non-operatively with a functional brace

Abstract: Functional bracing for the treatment of fractures of the humeral diaphysis is associated with a high rate of union with nearly normal elbow motion and some restriction of shoulder motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 14 publications
0
13
0
2
Order By: Relevance
“…Sarmiento et al ( 10 ), in 2000 demonstrated that using functional bracing for treating closed fractures of the humeral diaphysis resulted in a high rate of union due to the hydraulic impacts of the soft tissues. However, considerable limitations in shoulder and elbow mobility and certain residual angular deformities have been reported with functional bracing ( 5 , 9 , 10 ) which makes returning to usual daily activities difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarmiento et al ( 10 ), in 2000 demonstrated that using functional bracing for treating closed fractures of the humeral diaphysis resulted in a high rate of union due to the hydraulic impacts of the soft tissues. However, considerable limitations in shoulder and elbow mobility and certain residual angular deformities have been reported with functional bracing ( 5 , 9 , 10 ) which makes returning to usual daily activities difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Humeral shaft fracture is one of the common injuries encountered in orthopedic surgery ( 1 ) accounting for 1% - 5% of all fractures ( 2 - 4 ). Although nonoperative treatment of humeral shaft fracture is associated with satisfying clinical and functional outcomes in most cases ( 5 - 8 ), usually results in varus deformity and limitation of shoulder and elbow motion in some patients ( 5 , 9 , 10 ). Thus, orthopedic surgeons prefer operative management due to early return to function and low compliance of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, nonoperative treatment, such as functional bracing, has been considered an efficient method for isolated HSFs 1015. However, it might be associated with some complications, such as nonunion, angulation, malunion, shoulder impingement, skin abrasion, limited range of motion (ROM), and long-lasting treatment 7,1418…”
Section: Introductionmentioning
confidence: 99%
“…These include poor follow up rates, leading to amplification of proportions of non-union patients, who will present back to follow up more reliably than healed unions [ 9 - 11 ]. In addition, differences in protocols of applying a humeral brace across different countries and institutions have been observed in many studies, such as the use of U-slab, hanging cast, or backslab initially (and for different periods of time) before brace application, all of which could affect final outcomes [ 8 , 12 , 13 ]. In the literature, the reported time to union varies 8 to 30 weeks with an average of 10.7 weeks [ 1 , 2 , 12 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%